2020
DOI: 10.3389/fnmol.2020.552787
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Restraint Stress Led to Cognitive Dysfunction by NMDA Receptor-Mediated Hippocampal CA3 Dendritic Spine Impairments in Juvenile Sprague-Dawley Rats

Abstract: Although numerous studies have indicated that chronic stress causes cognitive dysfunction with the impairment of synaptic structures and functions, the relationship between cognitive deficits induced by repeated restraint stress and the level of NMDA receptors in the subregion of the hippocampus has been relatively unknown until now. In this study, 3-week-old male Sprague-Dawley rats were exposed to repeated restraint stress for seven consecutive days, their cognitive functions were evaluated through behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…In both sexes, the total number of GluN1 subunits increased in CA3 dendrites following CIS. Our data echoes the findings of others ( Sun et al, 2020 ), who showed that the total protein and mRNA levels of GluN1, GluN2A, and GluN2B were significantly increased in the CA3 region of the hippocampus in male Sprague Dawley rats exposed to repeated restraint stress (RRS) when compared to control. Additionally, the same experiment showed that the dendritic spine density in the CA3 region significantly decreased and that LTP was attenuated in male rats exposed to RRS ( Sun et al, 2020 ).…”
Section: Methodological Considerationssupporting
confidence: 91%
See 2 more Smart Citations
“…In both sexes, the total number of GluN1 subunits increased in CA3 dendrites following CIS. Our data echoes the findings of others ( Sun et al, 2020 ), who showed that the total protein and mRNA levels of GluN1, GluN2A, and GluN2B were significantly increased in the CA3 region of the hippocampus in male Sprague Dawley rats exposed to repeated restraint stress (RRS) when compared to control. Additionally, the same experiment showed that the dendritic spine density in the CA3 region significantly decreased and that LTP was attenuated in male rats exposed to RRS ( Sun et al, 2020 ).…”
Section: Methodological Considerationssupporting
confidence: 91%
“…Using in vivo microdialysis, it has been previously demonstrated that ten days of RRS results in lower glutamate levels in the male rat hippocampus compared to unstressed controls ( Macht et al, 2020 ). Even though prior studies have shown that RRS reduces glutamate levels in the male rat hippocampus, our study offers a different perspective by suggesting that the increase in GluN1 in all cellular compartments in male rats following CPP behaviors and CIS potentially increases the availability of receptors to bind glutamate, similar to Sun et al (2020) . Such a process may impact the lack of opioid receptor redistribution seen in our prior experiments in CIS males ( Reich et al, 2019 ).…”
Section: Methodological Considerationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, chronic isolation stress increased the corticosterone levels in both hippocampus and frontal cortex, whereas the glucose levels did not change in both these regions. In this way, some previous reports demonstrated the role of stress on impairments of excitability and long-term plasticity in other hippocampal regions (Artola, 2008;Radahmadi et al, 2014;Sun et al, 2020) and even with another type of stress (Hosseini Dastgerdi et al, 2021). Moreover, different factors affect the brain functions in stress conditions such as the severity, period and pattern, and nature of stressors (Radahmadi et al, 2015).…”
Section: [Figure 4] Discussionmentioning
confidence: 69%
“…Stress is known to evoke cognitive and emotional deficits [123]. In particular, stressinduced cognitive defects are attributable to the dysfunction of hippocampal channels or receptors [123,124]. Li et al reported that, in rats, acute stress led to cognitive failure, accompanied by the downregulation of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the hippocampal CA1 region [120], as well as significant decreases in the expression of PGC-1α, β-catenin, E4 promoter-binding protein 4 (E4BP4), and USP2.…”
Section: Nervous Systemmentioning
confidence: 99%